Applying grade inflation adjustment mechanism in an Ethiopian university: Differences in nominal and real grades - Wariyo, Lemecha Geleto; Kelbago, Roman Alemu (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Abstract-Grade inflation is a recognized problem in universities around the world. The factors underlying grade inflation are also discussed by studies. The objective of this study was: firstly, to observe the degree of grade inflation by analyzing the difference between nominal grades and real grades of students across departments. Secondly, the study analyzes the relationship between aptitude test scores and college GPA. In order to achieve these objectives, the first semester grades of all Wachemo university first batch third-year students (total 435 students: male 287 female 148) were collected from the registrar and the nominal and real grades were calculated. The Grieves method of real grade analysis formula was used to analyze the real grades. The findings of this study revealed that although there was no severity of grade inflation in the semester, 4 departments out of 12 departments registered inflated grades. The correlation between nominal and real grades of students is positive and strong indicating that real grades are grade-inflation adjusted nominal grades. There was a zero correlation between aptitude test scores and the college GPA in this study. The similarity of the grading system, and the similarity and the harmonization of the courses make the Grieve’s method of grade inflation adjustment mechanism to be applied in Ethiopian universities. In addition, mechanisms of adjusting grade inflation better have attention in Ethiopia in order to standardize grades from different universities to have a fairer and valid comparison of graduates for employment. Key words: Nominal grade, real grade, aptitude test scores